2018
DOI: 10.1016/j.schres.2018.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory deficits and psychosis-spectrum symptoms in 22q11.2 deletion syndrome

Abstract: Olfactory functioning is a promising biomarker for psychosis in 22q11.2 deletion syndrome (22q11DS) but has not been well studied to date. This is a pilot effort to evaluate the potential for tests of olfactory functioning to contribute to risk and resilience prediction in 22q11DS, and is the first study to evaluate relationships among olfactory deficits, cognition and psychosis-spectrum symptoms. Odor identification and discrimination were evaluated in 32 individuals with 22q11DS and 110 healthy comparison su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…[23][24][25][26][27][28] The most common congenital etiology by number of cases was 22q11.2 deletion syndrome with 98 total cases reported from 3 studies. 8,29,30 The most common etiology by number of reports was Kallmann syndrome (including its associations) with 24 studies describing a total of 64 cases. Reported etiologies have been categorized into whether the mechanism is hypothesized to be sensorineural, conductive, or mixed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26][27][28] The most common congenital etiology by number of cases was 22q11.2 deletion syndrome with 98 total cases reported from 3 studies. 8,29,30 The most common etiology by number of reports was Kallmann syndrome (including its associations) with 24 studies describing a total of 64 cases. Reported etiologies have been categorized into whether the mechanism is hypothesized to be sensorineural, conductive, or mixed.…”
Section: Discussionmentioning
confidence: 99%
“…As well, 6 studies described olfactory loss associated with autism spectrum disorder, accounting for 126 cases 23‐28 . The most common congenital etiology by number of cases was 22q11.2 deletion syndrome with 98 total cases reported from 3 studies 8,29,30 . The most common etiology by number of reports was Kallmann syndrome (including its associations) with 24 studies describing a total of 64 cases 31‐54 …”
Section: Discussionmentioning
confidence: 99%
“…Similar to affective symptoms, psychosis symptoms also had a partial mediated effect on the relationship between cognitive function and odor identification. Previous research indicates that odor identification dysfunction is present in schizophrenia patients (Moberg et al, 2006 ), first-degree relatives of schizophrenia patients (Turetsky et al, 2008 ), and subjects at risk for psychosis symptoms (Takahashi et al, 2018 ; Tang et al, 2018 ) and is believed to be highly associated with disease duration (Moberg et al, 2006 ), negative symptoms, and social-cognitive function (Corcoran et al, 2005 ). The anatomic proximity of the olfactory network to limbic structures provides a potential explanation for the relation between olfaction and affective symptoms, and may account for their shared dysfunction in various psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al [11] conducted a pilot study of 32 individuals to examine olfactory functioning as a possible biomarker for psychosis in 22q11.2DS. They showed that both odour identification and discrimination are significantly impaired in individuals with 22q11.2DS compared to healthy controls.…”
Section: Clinical Predictors Of Psychosis In 22q112dsmentioning
confidence: 99%